The chemistry book - Brunning, Andy; Cobb, Cathy; Extance, Andy; Farndon, John; Harris, Tim; Snedden, Robert (Big ideas simply explained., 2022)
"Arranged in chronological order, this . . . guide to more than seventy-five of the most historic moments in the science of chemistry, from the birth of atomic theory to the development of liquid crystal display screens, introduces the work of the scientists who have shaped the subject"--BTCat.